Aboriginal Capitalism: Is Resistance Futile or Fertile? - Atleo, Clifford Gordon (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2015)
Capitalism is everywhere. Many Indigenous leaders and scholars argue that it is unavoidable and must be engaged, despite capitalism’s sordid history as a means of assailing Indigenous lands and waters. I ask: Can capitalism be adapted to Indigenous values and principles? Can Indigeneity survive the encounter with capitalism? In this article, I look at the writings of three Indigenous academics — Robert Miller, Duane Champagne, and David Newhouse — and examine their positions on Aboriginal capitalism. Each author offers their perspective on the key problems facing Indigenous communities and individuals as well as the realities of tribal poverty and ubiquitous capitalist markets. How each author understands the key problems in “Indian Country” greatly determines their positions on potential solutions. I argue that capitalism cannot be Aboriginalized or Indigenized without radical, possibly transformative changes to core capitalist tenets. Similarly, I do not believe that Indigenous people and communities can actively engage with capitalist markets without radically changing their core values and principles. I acknowledge that change is a fact of life and society, but I do not believe that capitalism, as pervasive as it is, has to be the inevitable outcome of Indigenous desires for political, cultural, and economic autonomy. There are alternatives, and maybe some not yet imagined, but true alternatives that do not exploit our relatives and maintain balance and harmony in our homelands are worth our best efforts.